(untitled) (Scientific Journal for Publishing in Health Research and Technology, 2025)
The construction sector is experiencing rapid and increasing development every year. This rapid growth in concrete has led to the addition of chemicals that improve concrete performance and reduce the consumption of natural materials. Current development requires increasing the strength and durability of concrete to meet the requirements of modern construction. Natural and synthetic fibers are a good choice for improving concrete properties such as increasing compressive, flexural, and tensile strength. These fibers have been used since ancient times in different proportions and have proven effective in significantly enhancing compressive strength, flexural strength, tensile strength, and split tensile strength of cement. This study aims to determine the optimal percentage of fiber content as well as study the effect of high percentages of these fibers on concrete properties. Glass fibers (GF) and polypropylene fibers (PPF) were used in percentages: 0.5%, 1%, 1.5%, 2%, 2.5%, and 3% by weight of cement. Compressive, flexural, and tensile strengths of concrete were studied before and after fiber addition at a constant water-to-binder ratio of W/C = 0.5. Workability, compressive, flexural, and tensile strength were measured at 7 and 28 days. The results showed that workability decreased with increasing fiber content. Compressive strength was observed to decrease at all studied percentages, and the optimal fiber content for improving compressive strength was found at fiber contents less than 0.5% for both types of fibers. Compressive strength decreased with increasing fiber content, reaching its lowest values at 3% fiber content, which were 56.5% and 72% for glass fiber and polypropylene fibers, respectively. This decrease was accompanied by a decrease in split tensile strength. On the other hand, flexural strength increased for mixes containing glass fibers and polypropylene fibers with increasing fiber content. It reached its highest value at 1.5% fiber content with a 13.6% increase for glass fiber, and at 0.5% fiber content, with a 1.6% increase for polypropylene. Overall, glass fiber showed the best results for improving concrete properties.